State defense internalization in a university: Theory of planned behavior approach - Nurul Azizah; Nurul Retno Hapsari; Siti Ning Farida (Intelektual Pustaka Media Utama, 2022)
Universitas Pembangunan Nasional “Veteran” Jawa Timur (UPNVJT) is a university with state defense education’s characters. In practice, those character did not cover the academic field as a whole. Through the theory of planned behavior (TPB), the research carried out the process of internalizing state defense values in thesis writing as a form of character graduates. The research was conducted using a quantitative approach involving stakeholders at UPNJT, namely LP3M and head of department. Data were analyzed using partial least squares structural equation modeling (PLS-SEM) software. The results found that two TPB variables, namely attitudes and subjective norms in the organization, had an influence on the intention in implementing state defense values. The intention in implementing state defense values will influence perceived self-efficacy of state defense values. Meanwhile, the subjective norms of the perpetrators and the perception of behavioral control in accordance with the state defense values have no influence on the intention in implementing the state defense values.